2013
DOI: 10.1002/art.38181
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin‐10 in Endochondral Bone Formation in Mice: Anabolic Effect via the Bone Morphogenetic Protein/Smad Pathway

Abstract: Objective. Interleukin-10 (IL-10) is a pleiotropic immunoregulatory cytokine with a chondroprotective effect that is elevated in cartilage and synovium in patients with osteoarthritis. However, the role of IL-10 during endochondral bone formation and its mechanism of action have not been elucidated.Methods. IL-10 -/-mice and IL-10-treated tibial organ cultures were used to study loss and gain of IL-10 functions, respectively, during endochondral bone formation. Primary chondrocytes from the long bones of mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 48 publications
4
32
0
Order By: Relevance
“…IL-10 suppresses the osteogenesis of mouse bone-marrow cells via inhibition of TGF-b1 synthesis or production (13,56). IL-10 acts as a stimulator of chondrogenic or hypertrophic differentiation in endochondral bone formation in mice via activation of the BMP-Smad signaling pathway (49). However, we found that IL-10 did not affect the AKT, STAT3, or Smad signaling pathways in hBMSCs during osteogenic differentiation (see Supplemental Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…IL-10 suppresses the osteogenesis of mouse bone-marrow cells via inhibition of TGF-b1 synthesis or production (13,56). IL-10 acts as a stimulator of chondrogenic or hypertrophic differentiation in endochondral bone formation in mice via activation of the BMP-Smad signaling pathway (49). However, we found that IL-10 did not affect the AKT, STAT3, or Smad signaling pathways in hBMSCs during osteogenic differentiation (see Supplemental Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Dresner-Pollak et al (12) revealed that IL-10 knockout mice had reduced bone mass, increased mechanical fragility, and suppressed bone formation (11). Jung et al (49) found that the tibial growth plates of IL-10 knockout mice exhibited shortening of the proliferating zone. However, Van Vlasselaer et al (13,14) reported that IL-10 (2.5 3 10 3 U/ml) suppressed the osteogenic differentiation of mouse bone-marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…In OA, the level of IL-10 in cartilage and the synovium are elevated (23). Studies on synovial fluid levels of IL-10 in patients with MI are limited, and our study shows that patients with MI have higher levels of IL-10 in their synovial fluids in relation to patients with OA.…”
Section: Discussionmentioning
confidence: 99%
“…This is the probable mechanism for enhanced proliferating zone of growth plates in IL-10 expressing mice versus IL-10 knockout mice A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT (16). Since fracture repair recapitulates development in many aspects, IL-10 may also contribute to more robust callus formation in fracture repair.…”
Section: Accepted Manuscriptmentioning
confidence: 95%